GIZI, KESEHATAN GIGI-MULUT DAN DOKTER GIGI KECIL DI SDN 1 KETEWEL, SUKAWATI, GIANYAR - I Gusti Ayu Ari Agung; Dewa Made Wedagama; Ria Koesoemawati (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2018)
Nutrition and orodental health have significant relationship, especially in children who are experiencing the growth stage. Orodental health requires a balanced nutritional adequacy. Orodental health issues at SDN 1 Ketewel are low, this is supported by data from Puskesmas, as well as the Ketewel area of ​​Ketewel village Puskesmas Pembantu is not affordable to the whole Ketewel village. So as to result in lack of knowledge of nutrition and oradental health, finally affecting orodental health. This school is in dire need of garden of family medicinal plants (TOGA) for orodental health. UKS partners also do not have health books, posters and others about orodental health and other health books, such as nutrition and medicinal plants for oradental health. The implementation of science and technology activities involves counseling, training and mentoring of school students in the prevention of oraldental health. Furthermore, routinely monitor and evaluate the implementation of the program. The special target that has been achieved is the existence of a small dentist. sanctuary garden TOGAconservation. Responsible students for eradication, oradental health library, scientific publications, speakers in scientific meetings, teks books.